(untitled) - Hart, Lois Borland (New York, 2005)
Leadership development is self-development. The quest for leadership is first an inner quest to discover who you are. That is clearly the premise of this wonderful collection of developmental activities. They guide learners on that fascinating journey of self-awareness and self-confidence that can only come from experiencing something in themselves for themselves.
Tổ chức hoạt động trải nghiệm trong giảng dạy Tiếng Anh
Keywords: Lãnh đạo,Leadership; Dạy và học,Chương trình hoạt động,Study and teaching,Activity programs